Mackinder's Heartland Theory and Afterthoughts - (:unkn) unknown (MARMARA UNIV, 2017)
British geographer and geopolitician Halford Mackinder's Theory of Heartland is a popular work which attained its goal in those years. The French Geographer Lacoste says geography is about fighting referring to the importance of geography in wars. It is obvious that a commander who does not know geography cannot succeed. Mackinder's Theory of Heartland is a deception. The crafty British people did not appreciate the Mackinder's Heartland Theory. However, Mackinder is an important geopolitician and scientist for the English. An important scientist's theory was not put forward for the British but it was about containing its rival Germany in continental Europe. Indeed, the Germans embraced this theory tightly. In the Second World War, the Germans put Mackinder's Theory of Heartland into practice. But they failed. Germans believed this theory because they considered Mackinder as a genuine scientist. The English, however, used history as a trick throughout the history. Mackinder's Theory of Heartland was also a part of this trickery. Today's world should learn lessons from the past. We should no longer believe in the English tricks. The world should not be coaxed all too easily to the English tricks, but unfortunately, English games are still in practice all over the world. It seems like nobody has learned a lesson from them.
Keywords: Mackinder; theory; geography; political geography